Theory of the Legal Facts in the Context of Quantum Physics - Shafalovich, Hanna (Teisė, 2020)
It is considered that the theory of legal facts is one of the most conservative in jurisprudence, which is not confirmed on closer examination. This article is intended to draw parallels in the knowledge gained in law regarding legal substance and the knowledge gained in physics, primarily in quantum physics, regarding the structure of physical substance. As a result of the study, the author concludes that their positions are similar.
Keywords: theory of the legal facts; paradox of will; action; event; legal relationship; methodology